Characteristics of patients presenting with complications of abortion in a tertiary health facility in south-west Nigeria - A.O. Adeniji; O.O.A. Atanda; A.S. Adeyemi (South African Family Practice)
Objectives: Abortion is associated with significant healthproblem with short- and long-term complications that affect the quality of life of those who are fortunate enough to escape mortality. This study evaluated the population of patients with complications of abortion, identified the abortion providers and the pattern of contraceptive usage in these patients managed in our hospital, and suggests strategies on the required heath intervention.